2022
DOI: 10.1177/2156759x221105797
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of How School Counselors Adapted Their Delivery Due to COVID-Induced Disparities

Abstract: We utilized a mixed-methods design to understand how a national sample of 589 school counselors adapted their approach to address K–12 students’ academic, social/emotional, and career development during the COVID-19 pandemic. More specifically, we examined how COVID-19–induced disparities influenced school counselors’ delivery of services. We identified six themes using thematic analysis and conducted a t test to further understand what services and strategies counselors were actively using 6 months after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 18 publications
3
19
0
Order By: Relevance
“…These results indicated that individuals reported an increased likelihood of reporting making meaning of negative experiences compared with 3 months prior to the pandemic. Our result also seems to be consistent with Villares et al's (2022) main finding that most school counselors were able to maintain school counseling responsibilities 3 months after the onset of COVID-19.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results indicated that individuals reported an increased likelihood of reporting making meaning of negative experiences compared with 3 months prior to the pandemic. Our result also seems to be consistent with Villares et al's (2022) main finding that most school counselors were able to maintain school counseling responsibilities 3 months after the onset of COVID-19.…”
Section: Discussionsupporting
confidence: 92%
“…Role conflict and ambiguity have been reported to be common barriers when it comes to enactment of appropriate school counselor roles prior to the pandemic (Hilts et al., 2019), yet these barriers have been exacerbated by the COVID‐19 due to the priority to reacting to crisis (Levy & Lemberger‐Truelove, 2021; Villares et al., 2022). School counselors stressed the drastic transitions associated with the different modalities of learning, which contributed to their job to be primarily “putting out fires” (Limberg et al., 2022, p. 6). As such, there is a gap in the literature related to school counselors’ roles and perceptions at the systemic level.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in spring 2020, the spread of the novel coronavirus (COVID-19) forced nationwide school closures, which not only disrupted P–12 students’ learning but also school counselors’ ability to deliver comprehensive school counseling programs (ASCA, 2021; Limberg et al, in press). Throughout the pandemic, school counselors struggled to serve students, finding difficulty in accessing students in virtual environments and providing virtual counseling lessons on a day-to-day basis, while continuing to manage high caseloads, working to close opportunity and achievement gaps, and being assigned inappropriate duties (ASCA, 2021).…”
mentioning
confidence: 99%